Presenteeism Among Accounting Educators: The Role of Work-Family Conflict, Work Engagement, and Organizational Support in Covid-19 Pandemic - Sakina Nusarifa Tantri; Hana Norhamida; Agus Prasetyo (Jurnal Ilmiah Akuntansi, 2022)
This study depicts the work-family conflict and presenteeism model using moderating variables, namely work engagement and perceived organizational support. This study aims to investigate the effect of work-family conflict on presenteeism, and the moderating effects of work engagement and perceived organizational support on the relationship between work-family conflict and presenteeism. The method used in this study is quantitative with survey as the data collection method. Using questionnaire, the data of this study were collected from 68 participants. This study used moderated regression analysis to analyze the data. The finding of this study is that the work-family conflict significantly affects presenteeism. Meanwhile, work engagement and perceived organizational support are predictor moderating variables. This study implies that accounting educators and organizations should consider the presenteeism phenomena by understanding the work-family conflict, work engagement, and perceived organizational support.